Pengaruh Sales Promotion, Visual Merchandising, dan Store Atmosphere terhadap Impulsive Buying Konsumen Kedai Kopi - Livia Laurenza Lazarus; Adhi Prakosa; Arif Sudaryana (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This research aims to determine the influence of sales promotion, visual merchandising, and store atmosphere on impulsive buying at Kalola Space Coffee Shop in Yogyakarta. The study refers to consumers at the Kalola Space Coffee Shop in Yogyakarta. This research utilizes a quantitative research method. The sample used in this study consists of 80 respondents. Purposive sampling is the sampling strategy used in this study. The analysis used in this study is multiple linear regression, and hypothesis testing is conducted using the t-test, F-test, and R². The results of the testing prove that all three determinants of impulsive buying have a positive and significant influence.